Efecto del aloe vera en la gingivitis grado 1(leve) en perros domésticos en Latacunga - Herrera Mallitasig, Jenny Lucia (2015)
The American Academy of Periodontics defines gingivitis as a gum inflammation, caused by the action of substances derived from the bacteria plaque that is accumulated closed to the sulcus. The objective of this investigation was to determine the effect of the aloe on Gingivitis Grade 1 (mild) in home dogs, the investigation was carried out at the Planeta Vida Vet Clinic: the type of bacteria in the cavity was identified, the lasting time of aloe with respect to the effected produced and the costs of the application. 5 dogs were used with periodontal gingivitis grade1, before the application of aloe, an initial sample was taken by means of swabbing the tooth affected for the bacterial culture; then a dose of the gel or pulp from the aloe was applied in the mouth cavity, after an hour it was applied again, and progressively every hour taking for 24 hours in order to determine the effect of the antimicrobial effect of the aloe by means bacterial culture and clinic diagnose....